Decision support in addiction: The development of an e-health tool to assess and prevent risk of fatal overdose. The ORION Project. Issue 133 (September 2016) - Baldacchino, A.; Crocamo, C.; Humphris, G.; Neufeind, J.; Frisher, M.; Scherbaum, N.; Carrà, G.
Highlights: The ORION tool has been designed with the aim of being easy-to-use and informative to both patients and clinicians in various clinical settings. The ORION tool went through risk estimation processes using Delphi methods. The ORION tool utilised state of the art design systems to help engage the user. The ORION tool was conducted in four countries to assess feasibility of implementing the tool across various settings. Abstract: Background and objective: The application of e-health technology to the field of substance use disorders is at a relatively early stage, and methodological quality is still variable. Few have explored the extent of utilization of communication technology in exploring risk perception by patients enrolled in substance abuse services. The Overdose RIsk InfOrmatioN (ORION) project is a European Commission funded programme, aimed to develop and pilot an e-health psycho-educational tool to provide information to drug using individuals about the risks of suffering a drug overdose. Methods: In this article, we report on phase 1 (risk estimation), phase 2 (design), and phase 3 (feasibility) of the ORION project. Results: The development of ORION e-health tool underlined the importance of an evidence-based intervention aimed in obtaining reliable evaluation of risk. The ORION tool supported a decision making process aimed at influencing the substance users' self-efficacy and the degree to which the substance users' understand risk factors. Therefore, its innovative power consisted in translating risks combination into a clear estimation for the user who will then appear more likely to be interested in his/her risk perception. Conclusion: Exploratory field testing and validation confirmed the next stage of evaluation, namely, collection of routine patient samples in study clinics. The associations between risk perception of overdose, engagement with the ORION tool and willingness to alter overdose risk factors, in a clinical setting across various EU member states will further confirm the ORION tool's generalisability and effectiveness.